2003
DOI: 10.1161/01.str.0000058159.63950.ea
|View full text |Cite
|
Sign up to set email alerts
|

Associations of a Human G Protein β3 Subunit Dimorphism With Insulin Resistance and Carotid Atherosclerosis

Abstract: Background and Purpose-The C825T dimorphism of the gene encoding the human G protein ␤3 subunit (GNB3) is associated with hypertension and obesity. Although these findings suggest an association with insulin resistance and atherosclerosis, this hypothesis has yet been tested only partially. Methods-To investigate this hypothesis, the C825T dimorphism was determined in a population of 932 middle-aged white subjects of middle European (Austrian) origin. Insulin sensitivity was measured with the short insulin tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Due to their pivotal function in many cell types, variation in the genes encoding the subunits of G proteins has the potential to play a role in numerous clinical conditions. Specifically, investigators have studied possible associations of the frequent substitution of a C with a T nucleotide at position 825 in exon 10 in the gene encoding the G protein β3 subunit (GNB3), resulting in the silent Ser275Ser polymorphism, with hypertension [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and related cardiovascular phenotypes [16][17][18][19][20][21][22], and with obesity [22][23][24][25], psychological syndromes [26][27][28], type 1 diabetes complications (nephropathy, retinopathy and neuropathy) [29,30], type 2 diabetes [13,22,31,32], cancer [33] and various immunological responses [34]. The 825C>T polymorphism is associated with the occurrence of a splice variant with an in-frame deletion of 41 amino acids (from exon 9) including the fourth of seven Trp-Asp repeats, each consisting of approximately 40 highly conserved amino acids, which normally form a β-propeller peptide structure [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their pivotal function in many cell types, variation in the genes encoding the subunits of G proteins has the potential to play a role in numerous clinical conditions. Specifically, investigators have studied possible associations of the frequent substitution of a C with a T nucleotide at position 825 in exon 10 in the gene encoding the G protein β3 subunit (GNB3), resulting in the silent Ser275Ser polymorphism, with hypertension [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and related cardiovascular phenotypes [16][17][18][19][20][21][22], and with obesity [22][23][24][25], psychological syndromes [26][27][28], type 1 diabetes complications (nephropathy, retinopathy and neuropathy) [29,30], type 2 diabetes [13,22,31,32], cancer [33] and various immunological responses [34]. The 825C>T polymorphism is associated with the occurrence of a splice variant with an in-frame deletion of 41 amino acids (from exon 9) including the fourth of seven Trp-Asp repeats, each consisting of approximately 40 highly conserved amino acids, which normally form a β-propeller peptide structure [1].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, interindividual differences in BMI may also account for the observation that type 2 diabetic patients carrying the T allele had significantly improved insulin sensitivity compared with homozygous carriers of the C allele following an intervention-optimisation protocol [45]. However, this interpretation has been challenged by two studies of insulin sensitivity in which the T allele was associated with lower insulin sensitivity after adjustment for BMI [20,21]. Finally, two moderately sized studies have suggested an association of the 825T allele with type 2 diabetes [13,32].…”
Section: Introductionmentioning
confidence: 99%
“…222,223 Subtly reduced lipolysis in adipocytes in response to isoproterenol may help explain the association with overweight. 224 Other associations with the 825T variant include enhanced vasoconstriction in response to endothelin-1, norepinephrine, and angiotensin II, 225 but not an ␣-2 agonist 226 and a substantially increased response to sildenafil.…”
Section: ␣-Adducin (Add1)mentioning
confidence: 99%
“…Some investigators have tested association with insulin sensitivity, yielding heterogeneous results (Stefan et al 2004;Poch et al 2002;Brand et al 2003;Saller et al 2003;Wascher et al 2003). Most of these studies either relied on indirect estimates of insulin sensitivity (Brand et al 2003;Wascher et al 2003), or performed euglycemic, hyperinsulinemic clamp in very small samples (n=35, Poch et al 2002;n=30, Saller et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies either relied on indirect estimates of insulin sensitivity (Brand et al 2003;Wascher et al 2003), or performed euglycemic, hyperinsulinemic clamp in very small samples (n=35, Poch et al 2002;n=30, Saller et al 2003).…”
Section: Introductionmentioning
confidence: 99%